Pendampingan Penyusunan Dokumen KTSP Paud - Felisitas Ndeot; Theresia Alviani Sum; Petrus Redy Partus Jaya; Engelbertus Nggalu Bali; Maria Makdalena Ori (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
This service activity aims to provide assistance to the PAUD Santa Fransiska Asisi unit in compiling the KTSP document because the managers and teachers of the PAUD Santa Fransiska Asisi do not understand and have sufficient competence in compiling the KTSP document. The method used in this service activity is discussion and mentoring. The partners of this service activity are the managers and teachers of PAUD Santa Fransiska Assisi, totaling 3 people. The activity stages consist of (1) Studying the KTSP document; (2) Conduct discussions and assist the preparation of the PAUD KTSP document, (3) Observe the progress of the PAUD KTSP document preparation. The results of the service activities show that the managers and teachers of PAUD Santa Fransiska Assisi are able to prepare their own KTSP and produce a final KTSP document.